Challenges of Community Participation in Road Maintenance Projects: Evidence from Babati District Council, Tanzania - Juma Almasi Mhina; Rehema John Magesa (Journal of Social and Community Development, 2025)
Community participation is promoted as a strategy to enhance the sustainability and cost-effectiveness of road maintenance, particularly in developing nations like Tanzania. However, its implementation often faces significant challenges. This study evaluates the specific challenges hindering effective community participation in road maintenance projects within the Babati District Council, Tanzania. A mixed-methods approach was employed, collecting quantitative data through structured questionnaires from 399 community members selected via simple random sampling, and qualitative insights from key informant interviews with local leaders and TARURA Regional Manager. Data were analyzed using descriptive statistics and content analysis. The findings reveal that community participation is severely constrained by a combination of factors: a critical lack of awareness about projects, significant financial constraints among community members, weak coordination between local government and residents, an absence of technical skills and training, prevalent corruption and mismanagement of funds, and poor communication and transparency in planning. These challenges collectively undermine community trust, willingness, and capacity to engage meaningfully. The study concludes that for community participation to be effective, a multi-pronged strategy is essential.